A Clinicopathological Research of Skin Tumors from a Tertiary Care Centre in North India - Singhal, Rishabh; Hussain, Asma; Balkrishna, Nikam (Journal of Coastal Life Medicine, 2023)
Background: Understanding the clinicopathological characteristics of skin tumours is crucial for efficient diagnosis and management. Skin tumours are a major public health concern. In a tertiary care facility in North India, this study aims to look into the demographic distribution, anatomic site involvement, and tumour kinds of skin tumours. Methods: A retrospective analysis of 50 patients with cutaneous tumours was done. Data was gathered and analysed information on demographic traits, anatomic location involvement, and tumour kinds. Results: The head and neck region of the study population had a greater prevalence of skin tumours (50%), with males making up the bulk of the population (70%) as well. The most frequent kind of tumour (40%) was basal cell carcinoma, which was followed by squamous cell carcinoma (30%), melanoma (12%), sebaceous carcinoma (10%), and fibrosarcoma (8%). Conclusion: The study's findings shed light on the clinicopathological features of skin tumours in North India. The prevalence of BCC and SCC, the preponderance of males, and the higher head and neck incidence are consistent with earlier investigations. These discoveries advance our knowledge of skin tumours in this area and have implications for more effective methods of diagnosis and therapy. To better understand the underlying causes of these trends, more study is required